Lineage-Specific Disruption of Hematopoiesis by Oxaliplatin: Mechanisms of Erythropoietin Resistance and Immune Suppression - C. Sudlow, Leland; Du, Junwei; Shahverdi, Kiana; Zhou, Haiying; Y. Berezin, Mikhail (Journal of Hematology and Oncology Research, 2026)
Background Oxaliplatin, a widely used chemotherapeutic agent, is associated with hematologic toxicities such as anemia, leukopenia, and thrombocytopenia. Despite their clinical relevance, the molecular mechanisms underlying lineage-specific bone marrow suppression remain poorly understood. Methods We administered oxaliplatin to mice over eight weeks and performed RNA-sequencing (RNA integrity >8) on bone marrow alongside peripheral blood analysis and cytokine profiling. Transcriptomic data were analyzed to identify differentially expressed genes (DEGs) and enriched pathways. For that, we applied a thematic Gene Ontology (thematicGO) enrichment method that groups GO terms into biologically meaningful categories, such as hematopoietic lineage disruption, cell cycle arrest, and cytokine signaling. Results Oxaliplatin induced broad transcriptional suppression of erythropoiesis and lymphopoiesis, with 3,691 DEGs identified (FDR<0.05, |FC|>1.5). Upregulation of Cdkn1a and downregulation of E2f2 suggest G1/S cell cycle arrest, correlating with repression of key erythroid maturation genes (e.g., Spta1, Slc4a1, Alas2) and hemoglobin subunits (Hba-a1/2, Hbb-bs/t). Despite a ~3000-fold increase in renal Epo expression, bone marrow Epor was reduced, indicating erythropoietin resistance. B and T cell markers were also significantly downregulated, signifying a collapse in adaptive immunity. Notably, neutrophil populations were largely spared. Cytokine analysis in plasma revealed a pro-inflammatory shift with elevated TNF-α and reduced TGF-β, potentially exacerbating hematopoietic dysfunction. Conclusions Oxaliplatin induces a lineage-dependent suppression of hematopoiesis, driven by coordinated cell cycle arrest, metabolic stress, and disrupted cytokine signaling. RNA-seq analysis enabled integration of transcriptomic findings into coherent biological themes. These findings provide mechanistic insights into oxaliplatin’s hematologic toxicity linking bone marrow failure (potentially reversible) via interconnected inflammatory and metabolic pathways and may inform therapeutic strategies to minimize or restore myelosuppression in cancer patients.
Keywords: Oxaliplatin; Hematopoiesis; Chemotherapy-induced anemia; Erythropoietin resistance; Lineage-specific myelosuppression; Bone marrow transcriptomics; Immune suppression